Hypertrophic Cardiomyopathy as a Form of Heart Failure with Preserved Ejection Fraction: Diagnosis, Drugs, and Procedures - Sukriti Banthiya; Larissa Check; Jessica Atkins (US Cardiology Review)
Hypertrophic cardiomyopathy (HCM) is a complex and heterogeneous cardiac disorder characterized by cardiac hypertrophy disproportionate to loading stimuli (e.g. hypertension or aortic stenosis). Diagnosing HCM requires a thorough examination of clinical symptoms, with echocardiography as the key initial imaging tool. Multimodality imaging further supports diagnosis, helps assess left ventricular outflow obstruction, and aids in risk stratification for sudden cardiac death. The cornerstone of HCM management remains pharmacological therapy with β-blockers and calcium channel blockers serving as first-line agents to alleviate symptoms and reduce left ventricular outflow tract obstruction. More recently, cardiac myosin inhibitors have revolutionized the treatment paradigm for obstructive HCM. Procedural interventions such as septal reduction therapy are reserved for refractory cases. Genetic testing and risk stratification for sudden cardiac death play a critical role in treatment decisions, guiding further testing in first-degree relatives and ICD implantation in high-risk individuals. Exercise recommendations have evolved based on recent data, challenging traditional restrictions and emphasizing individualized plans.